Carbon Pricing in Islamic Economics: A Normative Analysis of Carbon Tax and Emissions Trading Systems - Asni Mustika Rani; Eva Fauziah; Atih Rohaeti Dariah (Research Synergy Foundation, 2025)
Climate change mitigation has encouraged the use of carbon pricing instruments, particularly carbon taxes and emissions trading systems (ETS). While these mechanisms are widely adopted for their economic efficiency, their ethical legitimacy remains contested in Muslim-majority contexts, where economic activities must conform to Islamic principles. This study examines the compatibility of carbon pricing instruments with Islamic economic jurisprudence, focusing on the ethical validity of ETS and carbon taxation. Using a qualitative normative-interpretive approach, the study analyzes Islamic legal sources, policy documents, and relevant literature, supported by expert consultation for analytical triangulation. The analysis is grounded in fiqh al-mu'amalah, Islamic fiscal ethics, maqasid al-shariah, and Sharia Enterprise Theory. Rather than measuring policy effectiveness empirically, the study evaluates carbon pricing based on transaction structure, ownership characteristics, and the presence of uncertainty or speculative elements. The findings indicate that emissions trading systems raise significant shariah concerns. Carbon allowances function as administrative permissions rather than tangible or usufruct-based assets, creating issues related to gharar and speculative trading. In contrast, carbon taxation shows stronger compatibility with Islamic fiscal principles when implemented transparently, proportionally, and with revenues allocated for public welfare and environmental protection. This study contributes by reframing, carbon pricing as an issue of ethical governance rather than technical efficiency. It concludes that carbon taxation, supported by maqasid al-shariah and Islamic fiscal principles, offers a more ethically defensible pathway for climate policy in Muslim-majority contexts.